1983
DOI: 10.1007/bf00542512
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of different methods of nebulising terbutaline

Abstract: The efficacy of terbutaline inhaled from different aerosol systems was studied in 13 adult asthmatics. Terbutaline 1 mg was delivered from a pressurised aerosol, 1 and 4 mg were inhaled from a nebuliser, 1 mg was inhaled through a pressurised aerosol with a pear-shaped, 750 ml spacer, and 1 mg was inhaled from a nebuliser with Intermittent Positive Pressure Ventilation (I.P.P.V.). An open, randomized, cross-over design was used. The bronchodilator effect was evaluated by recording hourly flow-volume curves and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1986
1986
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…A total of 16 papers were included for Review C, yielding 21 included studies due to Rochat and colleagues 1983a/b 250 being separate studies within the same paper and Cissik and colleagues 1986a/b/c, 136 Pedersen and Bundgaard 1983a/b, 251 and Zainudin and colleagues 1990a/b 244 describing multiple device/drug comparisons within a multiway crossover design.…”
Section: Methodological Quality Of Included Studiesmentioning
confidence: 99%
“…A total of 16 papers were included for Review C, yielding 21 included studies due to Rochat and colleagues 1983a/b 250 being separate studies within the same paper and Cissik and colleagues 1986a/b/c, 136 Pedersen and Bundgaard 1983a/b, 251 and Zainudin and colleagues 1990a/b 244 describing multiple device/drug comparisons within a multiway crossover design.…”
Section: Methodological Quality Of Included Studiesmentioning
confidence: 99%
“…[53][54][55] Twenty three studies in adults showed clinical equivalence for inhaler devices and nebulisers for the main pulmonary outcomes (FEV 1 and PEFR) and no evidence of significant difference in other outcomes. [56][57][58][59][60][61][62][63][64][65][66][67][68][69] Figure 5 shows the standardised mean difference of FEV 1 between nebulisers and hand held inhaler devices for the delivery of β agonists in stable asthma. 54 57-60 62 63 65-67 69-71 Updated searching identified two further studies.…”
Section: Effectiveness Of Nebulisersmentioning
confidence: 99%
“…Equally reliable MDI delivery can be assured using one of the newer valved aerosol-holding chamber systems attached to the MDI [25,[32][33][34], With in creasing emphasis on cost control in North American hospitals, this approach to aerosol therapy is gaining increasing support as the cost is about 50% less than that for nebulizer-delivered bronchodila tor solutions [35] while at the same time aerosol-borne nosocomial infections are virtually eliminated with the use of the MDI [36].…”
Section: Aerosol Generation and Deliverymentioning
confidence: 99%
“…There is now good evidence that aero sols delivered from MDIs are as effective as from other aerosol delivery systems [25,31], even in patients with life-threatening asthma, provided the 'usual' bronchodila tor dose is appropriately augmented (3-to 6-fold) [31]. Equally reliable MDI delivery can be assured using one of the newer valved aerosol-holding chamber systems attached to the MDI [25,[32][33][34], With in creasing emphasis on cost control in North American hospitals, this approach to aerosol therapy is gaining increasing support as the cost is about 50% less than that for nebulizer-delivered bronchodila tor solutions [35] while at the same time aerosol-borne nosocomial infections are virtually eliminated with the use of the MDI [36].…”
Section: Aerosol Generation and Deliverymentioning
confidence: 99%